Domesticated rice alters the rhizosphere microbiome, reducing nitrogen fixation and increasing nitrous oxide emissions - Chang, Jingjing; Costa, Ohana Y. A.; Sun, Yu; Wang, Jilin; Tian, Lei; Shi, Shaohua; Wang, Enze; Ji, Li; Wang, Changji; Pang, Yingnan; Yao, Zongmu; Ye, Libo; et al. (Nature communications, 2025)
Crop domestication has revolutionized food production but increased agriculture’s reliance on fertilizers and pesticides. We investigate differences in the rhizosphere microbiome functions of wild and domesticated rice, focusing on nitrogen (N) cycling genes. Shotgun metagenomics and real-time PCR reveal a higher abundance of N-fixing genes in the wild rice rhizosphere microbiomes. Validation through transplanting rhizosphere microbiome suspensions shows the highest nitrogenase activity in soils with wild rice suspensions, regardless of planted rice type. Domesticated rice, however, exhibits an increased number of genes associated with nitrous oxide (N 2 O) production. Measurements of N 2 O emissions in soils with wild and domesticated rice are significantly higher in soil with domesticated rice compared to wild rice. Comparative root metabolomics between wild and domesticated rice further show that wild rice root exudates positively correlate with the frequency and abundance of microbial N-fixing genes, as indicated by metagenomic and qPCR, respectively. To confirm, we add wild and domesticated rice root metabolites to black soil, and qPCR shows that wild rice exudates maximize microbial N-fixing gene abundances and nitrogenase activity. Collectively, these findings suggest that rice domestication negatively impacts N-fixing bacteria and enriches bacteria that produce the greenhouse gas N 2 O, highlighting the environmental trade-offs associated with crop domestication. Domestication of crops has boosted food production but increased dependence on fertilizers and pesticides. This study shows that wild rice harbors a higher abundance of nitrogen-fixing genes in the rhizosphere, while domesticated rice has more genes associated with nitrous oxide production.